PERTUMBUHAN DAN HASIL KEDELAI (Glycine max L.) PADA BERBAGAI CARA PEMBERIAN DAN DOSIS PUPUK UREA - Rusmana . (Jurnal Agroekoteknologi, 2011)
The experiments were conducted to determine soybean growth and yield responses to various ways of placement and dose of urea fertilizer. Experiments using a randomized block design factorial, with four replications. The first factor is the ways of placement of urea consists of two levels, namely: be placed next to the planting hole and placed along the bolt in between the rows of plants. The second factor is the dose of urea fertilizer consists of four levels, namely: 50 kg ha-1, 100 kg ha-1, 150 kg ha-1, and 200 kg ha-1. The results showed that the growth of soybean (plant height and number of leaves) showed no differences due to different ways of placement urea but soybean yield components and the yield showed differences due to different ways of placement of urea. Yield components (pod number, pod dry weight, and number of seeds) and yield (seed dry weight) of soybean is higher when the ways of placement of urea along the bolt is placed in between rows of plants compared with plants placed on the side. Differences urea dose given either 50 kg ha-1, 100 kg ha-1, 150 kg ha-1, and 200 kg ha-1 showed no difference on the growth and yield of soybean plants.Key words: doses, fertilizers placement, soybean, urea